Compression molding of pultruded carbon reinforced thermoplastic composites - Novo, P. J. (2020)
Historically, thermoset resins have dominated the composite industry but they start to be replaced by thermoplastics. In this study two different thermoplastic matrix carbon reinforced pre-impregnated materials were used, one produced in our laboratories (towpreg) and another obtained from coextrusion process (PCT). Carbon fibre and two different thermoplastic matrices (polypropylene and PRIMOSPIRE®) were selected for the production of the pre-impregnated materials. Heated compression moulding and pultrusion were the two manufacturing technologies used to obtain composite plates and profiles for study. The optimization of those processes was made by studying the influence of the most relevant processing parameters in the final properties of the produced carbon fibres thermoplastic matrix pre-impregnated materials and composites. The composite relevant mechanical properties were determined and the final composites were submitted to Dynamic Mechanical Analysis (DMA), Scanning Electron Microscope (SEM), optical microscopy and calcination tests. The determination of the fiber volume fraction of all studied composite was obtained comparing the results of thermogravimetric analysis (TGA), SEM and calcination tests.